(3ehYXI GHf eSYhO hMOjK GdMSf GdHUQis
(3ChdgG (B:s
(3CNHQfG GdbGVi CHh eMeO YWjI bGd ONdJ CfG hNeSI eYi Ydi QShd Gddg hSde hbO CUGHJfG eLGYI TOjOI , aeG PbfG efP s
(3BNQgG (B:s
(3bGdhG jG fHi Gddg , acja jONdI GdLfI , bGd jchf fUH Yjfg Je Pdc s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B11s
(3cJHJ GdYfGhjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs